EP584 Circulating tumour DNA to monitor tumour activity in endometrial cancer. (1st November 2019) - Moss, E; Gorsia, D; Collins, A; Whitton, A; Guttery, D
Abstract : Introduction/Background: Circulating tumour DNA (ctDNA) has been shown to be a sensitive method for monitoring cancer activity and stratifying patients likely to respond to chemotherapy in numerous solid tumours but its potential in endometrial cancer (EC) has not been established. Methodology: A prospective cohort study of women with high-risk, advanced and recurrent EC were recruited to have a blood test at every clinic visit until the patient completed follow up or is too unwell to continue. Clinical examination findings and impression, patient symptoms, imaging results and the site/date of recurrent disease were collected. DNA was extracted from FFPE tumour blocks, 3 ml of matched plasma for cell-free DNA (cfDNA) and buffy coat for germline DNA. DNA was sequenced using the Oncomine Pan-Cancer cfDNA targeted next generation sequencing (tNGS) panel (ThermoFisher) on an Ion S5 GeneStudio and analysed using Torrent Suite v5.6 and Ion Reporter v5.6. Results: Sixty-two women were recruited. To date 3 patients have recurred, 3 patients with advanced disease have progressed and a further 2 patients have died. Matched mutations were identified within the primary tumour and plasma using tNGS or digital droplet PCR (ddPCR). CtDNA was detected 3–6 months before clinical symptoms. Levels of cfDNA/ctDNA also accurately tracked EC response to chemotherapy and were able to determine chemotherapy response, as well as a lead-time to relapse, before a CT scan performed after Cycle 3. Conclusion: We have detected ctDNA in patients with high-risk/recurrent endometrial cancer (EC) using a simple, cheap blood test and have shown that it is possible to monitor chemotherapy response to give a real-time assessment of chemosensitivity as compared to waiting for changes on radiological imaging. These results on the utility of ctDNA as a biomarker for EC relapse open the door towards larger scale clinical trials investigating ctDNA for personalising EC treatment and follow-up. Disclosure: Nothing to disclose.